EFL Students' Learning Strategies in Speaking: A Case Study of Sixth Semester at English Education Department, Muria Kudus University - Felisa, Felisa; Utomo, Slamet; Romadlon, Farid Noor (Journal Prakarsa Paedagogia, 2023)
Speaking is the most basic activity in life. Speaking is defined as an activity carried out by someone to communicate, exchange ideas, express views, and convey other life information. Speaking is also included in matters that are significant in various aspects of life in the sense that speaking is an important thing that must be done and must be mastered. Speaking skills occupy a very important position because speaking skills demonstrate students' communicative abilities. Therefore, this study aims to find out the students’ learning strategies in speaking of sixth semester at English Education Department in the academic year 2022/2023 and how do the students apply it. The design of this research is qualitative research. The participants of this research were the sixth semester students of Muria Kudus University in the academic year 2022/2023. The researcher used questionnaire and interview as the instruments the collect the data. The results of this research showed that all the types of learning strategies are used in terms of speaking English, namely Memory strategies, Cognitive strategies, Compensation Strategies, Metacognitive strategies, Affective strategies, and Social strategies. Based on all the strategies used by the students, its indicated that the students prefer to used indirect learning strategies than Direct learning strategies. The Direct learning strategies that used by the students to improving English speaking skills were Compensation strategies (69,8%), Cognitive Strategies (64,9%), and Memory Strategies (63,7%). Indirect learning strategies that used by the students were Affective Strategies (71,3%), Social strategies (71,1%), and Metacognitive Strategies (67,8%). In improving the ability to speak English, sixth semester students do many ways such as writing new vocabularies in the book, practicing and learning some new words, using gestures and improvising when they forget an English word, and evaluating the progress in speaking English.